Chemical Constituents of Indonesian Micromelum minutum Leaves and Their Cytotoxicity Against MCF-7 and 4T1 Breast Cancer Cells - Ratna Asmah Susidarti; Edy Meiyanto; Muthi' Ikawati; Normaidah; Nurramadhani Armada Sida (Institute for Research and Community Services (LPPM) ITB, 2021)
Micromelum minutum is used widely in traditional folk medicine. Although this species has been investigated extensively and several bioactive compounds have been isolated, little work has been done on Indonesian M. minutum. This research aimed to study the chemical constituents and biological activities of M. minutum cultivated in Bantimurung Bulusaraung National Park, South Sulawesi, Indonesia. The isolated compounds were assessed for their cytotoxicity towards MCF-7 and 4T1 cell lines by MTT method. The dried ground leaves of M. minutum were sequentially macerated with n-hexane, ethyl acetate, and methanol. The n-hexane and ethyl acetate extracts contained a flavonoid 5,7-dihydroxy-3,4',8-trimethoxyflavone (1) which inhibited MCF-7 and 4T1 cell viability by 50% at concentrations of 369±8 and 227±5 µM, respectively. Further separation of the ethyl acetate extract by column chromatography yielded acetyldihydromicromelin A (2) and a mixture of dihydromicromelin A (3) and dihydromicromelin B (4), which were not active toward MCF-7 and 4T1 cells.